ANALISIS PERBANDINGAN PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH YANG MEMPEROLEH OPINI WAJAR TANPA PENGECUALIAN DAN WAJAR DENGAN PENGECUALIAN - Vita Fitria Sari (Jurnal Praktik Bisnis, 2015)
Disclosure is one criteria that used by BPK RI to obtain opinion of audited local government’s financial statement. This study aimed to compare the financial disclosure of local government’s financial statement which received unqualified opinion and qualified opinion from BPK RI. Banyuasin regency (whose received unqualified opinion) and Bojonegoro regency (whose received qualified opinion) were chosen as participant. This study used content analysis, and coding based on Indonesia’s Government Accounting Standard (PP No.24 Tahun 2005). Based on participant’s data both Banyuasin regency and Bojonegoro regency already fullfil sufficient disclosure for Balance Sheet, Budgetary Reports and Cash flow Statement with no difference between them eventhough they received difference audit opinion. But on note of financial statement, there were some difference whereas Bojonegoro regency discloses more information than Banyuasin regency. It showed that sufficient disclosure didn’t guarantee audit opinion, because there are others criteria that BPK used to obtain opinion of audited local government’s financial statement. Keywords: disclosure, local government financial statements, unqualified opinion, qualified opinion, content analysis.